Paediatric palliative care: a survey of paediatricians and family practitioners. Issue 3 (31st May 2012) - Straatman, Lynn; Miller, Tanice
Abstract : Background: Paediatric palliative care focuses on the enhancement of the quality of life for a child and family through a combination of active and compassionate therapies intended to comfort and support the child and family who are living with a life-threatening illness. The purpose of this study was to assess the experience with and confidence in providing paediatric palliative care of practicing family/general practitioners (GPs) and paediatricians. In addition, the learning needs, modes of learning and their methods of coping/self-care were questioned. Methods: Two hundred paediatricians and GPs in the province of British Columbia were randomly selected to participate in a mailed survey. The survey consisted of three categories: demographic information, experience and knowledge of paediatric palliative care, educational needs and preferences for learning and provision of their own self-care. Results: The response rate of completed surveys was 56.5%. Only 40.1% of respondents felt their knowledge and experience were adequate. Overall, 73.5% of the respondents reported that they would like to learn more about paediatric palliative care. Over 53% of those surveyed preferred that learning be offered remotely through either internet or correspondence. Seventy-four per cent of respondents expressed they had adequate or very adequate self-care strategies to meet their own needs of well-being. Conclusions: The results of the survey will guide the paediatric palliative care community to design programmes that will better educate practicing physicians and future physicians about paediatric palliative and end of life care, healthcare services and family communication and support.